Factors Influencing Compliance with Iron Supplementation Among Female Adolescents in Senior High Schools, Samarinda City, 2025 - Indriani, Dilla C; Ramadhani, Reza W; Nurlela, Siti; Irirwanas, Intannia D; Zakki Saefurrohim, Muhamad; Azmiardi, Akhmad; Pakki, Irfansyah Baharuddin; Siswanto, Siswanto; Arfandi, Muh. Amri; Risva, Risva (Universitas Mulawarman, 2025)
Anemia in adolescent girls is a significant health problem due to increased iron requirements during puberty. Iron supplements are an important intervention, but previous studies have shown that 58.4% of adolescent girls have low compliance rates. This study aims to analyze the relationship between knowledge and attitudes toward iron supplement consumption among high school students in Samarinda City. This study used a cross-sectional design involving 466 respondents from three secondary schools. Data were collected through an online questionnaire covering knowledge, attitude, and TTD consumption variables. Results showed that 47.2% of respondents had very good knowledge and 90.3% had a positive attitude. Bivariate analysis showed no significant relationship between knowledge and TTD consumption (OR = 1.039; 95% CI: 0.680–1.587; p = 0.860). Conversely, attitude showed a significant relationship, where students with negative attitudes were less likely to consume TTD (OR = 1.613; 95% CI: 1.052–2.471; p = 0.028). These findings indicate that attitude has a greater influence than knowledge in promoting TTD consumption behavior. Interventions to improve TTD consumption compliance should focus on fostering positive attitudes among adolescent girls.